Describing spoken English - Kreidler, Charles W., 1924- (Routledge, 1997)
The pronunciation of English. Speech. The structure of language. English consonants. English vowels. Syllables. Strong and weak syllables. Word stress. Stress in compound words and phrases. The role of accent in discourse. Intonation. Morphemes that vary in form.